Faktor-faktor yang memengaruhi kekambuhan gastritis - Septiana, Annisa; Andora, Novika; Erwin, Tubagus (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Gastric mucosa can experience acute or chronic inflammation known as gastritis. In 2021, gastritis attacked 40-50% of the world's population, as reported by the World Health Organization (WHO). According to data from the Ministry of Health, gastritis ranked sixth in 2018, covering 60.86% of all hospitalizations (a total of 34.580). Patients with gastritis will have productivity and quality of life that are disrupted by this disease. In addition to disrupting daily activities, this disease also has an impact on the social and economic welfare of sufferers. Purpose: To determine the factors that influence and are associated with gastritis recurrence. Methods: This study used a cross-sectional method with a quantitative descriptive research design. The participants of the study were individuals who were treated at the Kotagajah Health Center with gastritis. The sampling technique used incidental sampling, so that a sample of 98 people was obtained. Data collection was carried out using a questionnaire containing questions about food and the use of OAIN. Results: The prevalence of unhealthy eating patterns was 81 (82.7%) and the prevalence of OAIN use variables was 72 (73.5%) in respondents. The results of the study showed a correlation between gastritis recurrence and factors indicated by a p value <0.05 obtained from the chi-square statistical test. Conclusion: Gastritis recurrence is associated with several factors, including poor diet and NSAID use. The results of the study stated that there was a significant relationship between diet and gastritis recurrence between the two variables and the results of the chi square test of the NSAID use variable also showed a significant relationship between the two variables. Keywords: Diet; Recurrence of Gastritis; Use Of Oains Pendahuluan: Mukosa lambung dapat mengalami peradangan akut maupun kronis yang dikenal dengan sebutan gastritis. Tahun 2021 gastritis menyerang 40-50% dari populasi dunia, sebagaimana dilaporkan oleh Organisasi Kesehatan Dunia (WHO). Menurut data Kementerian Kesehatan gastritis menduduki peringkat keenam pada tahun 2018 yang mencakup 60.86% dari seluruh kasus rawat inap (total 33.580). Pasien dengan penyakit gastritis akan memiliki produktivitas dan kualitas hidup yang terganggu oleh adanya penyakit ini. Selain mengganggu aktivitas sehari-hari, penyakit ini juga berdampak pada kesejahteraan sosial dan ekonomi penderitanya. Tujuan: Untuk mengetahui faktor-faktor yang mempengaruhi dan berhubungan dengan kekambuhan gastritis. Metode: Penelitian ini menggunakan metode cross-sectional dengan desain penelitian deskriptif kuantitatif. Partisipan penelitian adalah individu yang berobat ke Puskesmas Kotagajah dengan penyakit gastritis. Teknik pengambilan sampling menggunakan sampling insidental, sehingga diperoleh sampel sebanyak 98 orang. Pengumpulan data dilakukan dengan menggunakan kuesioner yang berisi pertanyaan tentang makanan dan penggunaan OAIN. Hasil: Prevalensi pola makan tidak sehat sebesar 81 (82.7%) dan prevalensi variabel penggunaan OAIN sebesar 72 (73.5%) pada responden. Hasil penelitian menunjukkan adanya korelasi antara kekambuhan gastritis dengan faktor-faktor yang ditunjukkan dengan nilai p<0.05 yang diperoleh dari uji statistik chi-square. Simpulan: Kekambuhan gastritis berhubungan dengan beberapa faktor, diantaranya yaitu pola makan yang buruk dan penggunaan Oains. Hasil penelitian menyatakan adanya hubungan pola makan dengan kekambuhan gastritis secara signifikan antara kedua variabel tersebut dan hasil uji chi square variabel penggunaan oains juga menunjukkan adanya hubungan yang signifikan antara kedua variabel tersebut. Kata Kunci: Kekambuhan Gastritis; Penggunaan Oains; Pola Makan